REVITALISASI SEJARAH LOKAL DALAM PEMBELAJARAN IPS: Kebutuhan Guru pada Era Diferensiasi Kurikulum - Hartanto, Deni (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2025)
This study examines the needs of Social Studies teachers in implementing differentiated instruction that integrates local history from Langkat Regency at MTsS Prof. Dr. H. Mohd. Hatta. Using a qualitative phenomenological approach, data were collected from the principal, two teachers, and students across three classes through interviews and document analysis. Findings show that teachers recognize the value of local history integration but face limited resources, insufficient training, and lack of instructional tools. Nevertheless, differentiated instruction based on local historical content is seen as highly promising. The study recommends strengthening school policies, teacher capacity, and resource development to support locally grounded, differentiated Social Studies learning.